PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATERI MASALAH-MASALAH EKONOMI MELALUI PEMBELAJARAN KOOPERATIF MODEL ICE BREAKING - Hastiyaningsih, Anik (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah (BAPPERIDA) Kabupaten Pati, 2018)
ENGLISHThe learning outcomes on the economic issues material of the students in the grade 10th social-3 SMAN 3 were low. It was indicated that the students had low motivation to learn that material. Therefore, the teacher applied ice breaking as a learning method to promote students’ motivation and learning outcomes. This research aimed to compare students’ motivation and learning outcomes on economic issue material before and after the application of ice breaking model. It used action class approach, in which 36 students participated as respondents. It comprised two cycles, which each cycle consisted of four stages, namely: planning, action, observation, and reflection. Data were collected through test and observation and then were analyzed using the quantitative-qualitative descriptive method. The research concluded: (1) the students showed higher motivation on learning activities after the researcher applied ice breaking method. They paid more attention and were active answering questions; and (2) there was the increase in the students' learning outcomes, i. e, 62.08 on precycle; 70.28 on cycle I; and 76.81 on cycle II. Furthermore, the number of students passed the standard of minimum completion (KKM) increased as well, that were 10 students in precycle, 20 students in cycle I, and 31 students in cycle II. INDONESIAHasil belajar kelas X IPS3 SMAN 3 tentang materi masalah-masalah ekonomi cenderung rendah. Para siswa memiliki motivasi yang rendah dalam mempelajari materi tersebut. Oleh karena itu, guru menerapkan metode belajar ice breaking untuk meningkatkan motivasi dan hasil belajar siswa. Tujuan penelitian adalah membandingkan motivasi dan hasil belajar siswa sebelum dan sesudah penggunaan metode ice breaking. Penelitian ini menggunakan metode tindakan kelas, dengan menyertakan 36 siswa sebagai subjek penelitian.peneltiandilakukan dalam dua Siklus, dimana setiap Siklus terdiri dari empat tahap, yaitu perencanaan, penerapan, observasi, dan refleksi. Pengumpulan data menggunakan tes dan observasi, selanjutnya data diolah dengan metode deskriptif kuantitatif-kualitatif. Hasil penelitian adalah (1) para siswa menunjukkan motivasi yang lebih tinggi setelah penerapan ice breaking, tercermin dalam perhatian yang lebih baik selama pembelajaran dan keaktifan dalam menjawab soal; dan (2) terjadi peningkatan hasil belajar, yaitu 62,08 pada kondisi awal, 70,28 pada Siklus I, dan 76,81 pada Siklus 2. Selain itu, jumlah siswa yang memenuhi KKM juga meningkat, yaitu 10 siswa pada kondisi awal,20 siswa pada Siklus I, dan 31 siswa pada Siklus II.